Kebijakan Ham Berdasarkan Peraturan Perundang-Undangan dalam Pemberian Remisi dan Pembebasan Bersyarat Kepada Koruptor - Jhansen Siahaan; Patricia Rinwigati (LPPM Universitas Ekasakti Padang, 2023)
In the current period, human rights are highly respected, as can be seen from the strategy of enforcing human rights itself by guaranteeing human rights for convicts of criminal acts of corruption who have been imprisoned for a long or short time, therefore they must also pay attention to their human rights such as welfare while serving. detention period. This scientific journal research method uses a normative research type. Based on the results of the research analysis, remission and conditional release are a form of protection from the state for the human rights of convicts of criminal acts of corruption, with restrictions by the state on their freedom, such as conditional release which can be granted after serving a minimum of 2/3 of the criminal term and has served well. both during the period of detention, with a minimum sentence of nine months. Where the granting of remissions and parole is still given. There are several other rights, firstly, prisoners have the right to worship in accordance with their religion, secondly, prisoners have the right to receive treatment, thirdly, to receive health services, fourthly, to receive education, fifthly, the right to express their complaints. Sixth, get reading material, seventh, get wages for the work you have done. Eighth, the right to receive family visits. And prisoners have the right to obtain other rights in accordance with applicable legal regulations.